The Politics of Utopia: Walter Pater’s “Lacedaemon” - Bénédicte COSTE (E-REA)
Walter Pater is not usually considered as a politically committed writer, neither is Aestheticism of which he was the gifted theoretician with The Renaissance (1873). Although the political commitments of the Aesthetic movement have been questioned over the last two decades, both by including women aesthetes, and by re-evaluating the movement’s dissemination among the middle classes, discussion of Pater’s political ideas is almost non-existent. His Plato and Platonism (1893) is however not so remote from politics since it discusses Plato’s political philosophy. In particular, “Lacedaemon”, the chapter devoted to Sparta, enables Pater to intervene in the political debate from an original standpoint. His political commitment appears as a meditation upon a specific form of citizenship, historically remote, and presented through a literary genre that was used for the first (and last) time in his writings—utopia, or rather dystopia, when it appears that the city-state is devoid of man’s essential characteristic: his paraleipomenon.